PEROLEHAN TANAH OBYEK REFORMA AGRARIA (TORA) YANG BERASAL DARI KAWASAN HUTAN: PERMASALAHAN DAN PENGATURANNYA - Nurlinda, Ida (Veritas et Justitia, 2018)
Agrarian reform is in essence a government policy attempting to restructure land ownership and control.  President Jokowi’s government set the target of 9 million hectares of which 4.1 million hectares is classified formerly as forest land.  It was and still is no easy task. But this agrarian reform, involving mostly change of ownership of forest land and redistribution, is considered necessary as part of effort to guarantee society’s welfare. This article purports to analyse the legal framework of forest land release and related problems. To do that a juridical dogmatic approach will be used and with secondary data as primary source of information.  The main finding of this research is that real problems arises in the context of implementing the Environmental and Forest Ministerial Decree Number180/Menlhk/Setjen/kum.1/4/2017 which provides guidance in regard the procedure and requirements to be met for forest land release. In the case that in the process, land ownership dispute arose, stakeholders should seek guidance from Presidential RegulationNumber  88/2017 regarding Settlement of Land Management/Ownership in Forest Land.